SPATIAL PATTERN IN BETA DIVERSITY OF ECHINOIDEA AND ASTEROIDEA COMMUNITIES FROM THE COASTAL AREA OF TOMIA ISLAND, WAKATOBI MARINE NATIONAL PARK, SOUTHEAST SULAWESI, INDONESIA - Kangkuso Analuddin; Nasaruddin Nasaruddin; Andi Septiana; Wa Ode Sarliyana; Agus Nurlyati; Wa Masa; Saban Rahim (SEAMEO BIOTROP, 2015)
The present study was aimed to elucidate the spatial pattern in the beta diversity of marine bentic for Echinoidea and Asteroidea that assemblages the coastal area of Tomia Island, Wakatobi Marine National Park, Indonesia. The two transect lines of 460 and 260 m in length with small quadrats of 1m2 wide were placed at the open and unopen beaches perpendicularly to the coastlines. The important value index and similarity index SI of organisms on these taxa were estimated in each the transect. Echinometra mathaei was the most dominant Echinoidea at open and unpen beaches, while Protoreaster nodusus was the most dominant Asteroidea at both areas. Most of SI values of Echinoidea at open beach were estimated less than 50%, which was lower than SI values that of organisms at unopen beach. On the other hand, most of SI values of Asteroidea at both areas were estimated more than 70% representing high similarity degree of its species composition among sites. The disimilarity index of organisms in the taxa of Echinoidea and Asteroidae was increased significantly as increasing the distance of among stands, which suggested that pettern in beta diversity of these taxa was associated with the spatial heterogenity.